2019
DOI: 10.1080/09712119.2019.1590205
|View full text |Cite
|
Sign up to set email alerts
|

Creatine or guanidinoacetic acid? Which is more effective at enhancing growth, tissue creatine stores, quality of meat, and genes controlling growth/myogenesis in Mulard ducks

Abstract: This study aimed to determine the effectiveness of guanidinoacetic acid (GAA) with or without methionine (Met) compared to creatine (CREA) at enhancing duck's performance, restoring tissue CREA and improving meat quality. Mulard ducklings (n = 250) were randomly assigned to control (without additives), or control plus CREA, GAA, GAA + 0.2%Met (GAAMet0.2) or GAA + 0.4%Met (GAAMet0.4) groups in a completely random experimental design. Dietary supplementation of CREA or GAA significantly increased (P < 0.05) over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 35 publications
4
28
1
Order By: Relevance
“…Dietary GAA has obtained interest to promote higher muscle creatine levels (Majdeddin et al, 2018;Ibrahim et al, 2019), which, in turn, have been associated with improved energetics (Ostojic, 2017;Sadra et al, 2018) and significant increases of high phosphate energy metabolites in broilers supplemented with GAA (Michiels et al, 2012;De Groot et al, 2018;Majdeddin et al, 2018). Improvements in energy utilization have been related to better feed utilization (Khajali et al, 2020).…”
Section: Gaa Used As Feed Additive For Poultrymentioning
confidence: 99%
See 4 more Smart Citations
“…Dietary GAA has obtained interest to promote higher muscle creatine levels (Majdeddin et al, 2018;Ibrahim et al, 2019), which, in turn, have been associated with improved energetics (Ostojic, 2017;Sadra et al, 2018) and significant increases of high phosphate energy metabolites in broilers supplemented with GAA (Michiels et al, 2012;De Groot et al, 2018;Majdeddin et al, 2018). Improvements in energy utilization have been related to better feed utilization (Khajali et al, 2020).…”
Section: Gaa Used As Feed Additive For Poultrymentioning
confidence: 99%
“…In the same way, Nasiroleslami et al (2018) had reported higher CK activity in GAA-supplemented broilers than in the control group. In a more recent publication, Ibrahim et al (2019) demonstrate that dietary supplementation of GAA plus 0.4% methionine (GAA + 0.4% Met) increased carcass and breast meat yield and improved plasma and muscle creatine more than dietary creatine itself in mulard ducks.…”
Section: Gaa Used As Feed Additive For Poultrymentioning
confidence: 99%
See 3 more Smart Citations